CHURUG FASHION 1907–1937 OR A REPORT OF A MUSEUM INSIDER - Radisavlјević Katarina (Bulletin of the Institute of Ethnography SASA, 2022)
The paper starts from the critique of the opinion that has developed in the 21st century within the framework of Serbian ethnological / anthropological science, and is related to the study and interpretation of traditional clothing of the rural population. Namely, the work of ethnologists / curators is criticized as the romantic relics in Serbian museology, who is consisted of the endless description of clothing and decorations on them. This paper has intention to point out some different ways of thinking on the Collections of traditional clothing in Serbia. The openness of anthropology to other humanities can help us find new ways to interpret the artefacts of the past. In terms of the use of other approaches, we primarily mean the theory of fashion, gender studies, cultural history, but also some of the anthropological approaches to clothing that are less used in our country, such as the theory of cultural authentication. Also, in the paper has been pointed out on the terminolgy distinction between traditional clothes / folk costume / folk dress and fashion clothes which has existed in the anthropology of clothing for a long time, and refers to diferent lines of identity and function wearer of clothes. This terminological distinction is very important in the initial interpretation of artefacts that can be found in clothing collections today. In the second part of the paper author applies the theoretical concept named The Dress detective, by Mida and Kim, on an apron from the Collection of Folk Costumes and Clothing of the Museum of Vojvodina. Analysis of the apron from village Čurug brought the author to the new concept of scientific approach to the museum objects, especially those made of textile.